Joy in medicine? : what 100 healthcare professionals have to say about job satisfaction, dissatisfaction, burnout, and joy - Shapiro, Eve (New York : Productivity Press, 2021)
Eve Shapiro has been writing about patient-centered care, physician-patient communication, and relationships between doctors and their patients since 2007. In Joy in Medicine? What 100 Healthcare Professionals Have to Say about Job Satisfaction, Dissatisfaction, Burnout, and Joy, Eve turns her attention to those on the healthcare delivery side of this "sacred interaction." These healthcare professionals share their enthusiasm, joys, frustrations, disappointments, insights, advice, stories, fears, and pain, explaining how it looks and feels to work in healthcare today no matter who you are, where you work, or what your position is in the organizational hierarchy. The healthcare professionals who provide patient care deserve our collective interest in their humanity. Without some insight into who they are and the forces with which they struggle every day, we cannot fully appreciate the obstacles to providing the care we all want for ourselves and our families during the best of times, let alone in the uncertain times that lie ahead.
DiGioia, MD, orthopaedic surgeon and medical director of the UPMC Magee-Womens Hospital and the UPMC Innovation Center Connie E., DNP, Level 2 staff nurse at a quaternary care pediatric hospital and assistant professor of nursing Tyler M., MD, chief medical officer for an integrated health system Joseph B., MD, retired professor, researcher, and practicing gastroenterologist; president of a board review company in gastroenterology; and head of a monthly gastroenterology journal club Adam B., MD, pediatric pulmonologist and sleep specialist at a quaternary care children's hospital Caitlin G., MSN, assistant clinical professor, hospital and home care nurse, and PhD student Monica T., MD, Assistant Professor of Pediatrics and Attending Neonatologist at a Quaternary Care Pediatric Hospital Walter G., MD, general surgeon Nancy W., RN, PhD, nurse
OCLC-licensed vendor bibliographic record.
Keywords: Medical personnel -- Job satisfaction; Medical personnel -- Job stress; Physician and patient; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Workplace Culture